2007
DOI: 10.1029/2007jc004227
|View full text |Cite
|
Sign up to set email alerts
|

Refraction and reflection of infragravity waves near submarine canyons

Abstract: [1] The propagation of infragravity waves (ocean surface waves with periods from 20 to 200 s) over complex inner shelf (water depths from about 3 to 50 m) bathymetry is investigated with field observations from the southern California coast. A waveray-path-based model is used to describe radiation from adjacent beaches, refraction over slopes (smooth changes in bathymetry), and partial reflection from submarine canyons (sharp changes in bathymetry). In both the field observations and the model simulations the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Although most of the free IG wave energy is refractively trapped or dissipated at coastlines, some of the energy leaks into the deep ocean [ Munk et al ., ; van Dongeren and Svendsen , ; Thomson et al ., ; Dolenc et al ., ; Uchiyama and McWilliams , ]. Once there, free IG waves can propagate across the ocean basin with little attenuation [e.g., Snodgrass et al ., ; Shillington , ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the free IG wave energy is refractively trapped or dissipated at coastlines, some of the energy leaks into the deep ocean [ Munk et al ., ; van Dongeren and Svendsen , ; Thomson et al ., ; Dolenc et al ., ; Uchiyama and McWilliams , ]. Once there, free IG waves can propagate across the ocean basin with little attenuation [e.g., Snodgrass et al ., ; Shillington , ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Wave-induced pressures and velocities were measured at 28 locations between the 5.0-m isobath and the shoreline [Thomson et al, 2006[Thomson et al, , 2007. Sensors were sampled at 2 or 16 Hz for 3072 s (51.2 min) starting every hour.…”
Section: Measurementsmentioning
confidence: 99%
“…Previous studies also have shown that nearshore circulation, including the locations of rip currents, can be controlled by nonuniformities in the offshore (i.e., outside the surfzone) bathymetry [Long and Ö zkan-Haller, 2005]. Here, the effect of strong alongshore variations in the incident wavefield (caused by an offshore submarine canyon [Long and Ö zkan-Haller, 2005;Magne et al, 2007;Thomson et al, 2007]) on setup and on alongshore flows in the surfzone is examined using field observations and simplified one-and two-dimensional momentum balances. After the theories are outlined (section 2) and the observations are described (section 3), the results are presented (section 4) and conclusions are given (section 5).…”
Section: Introductionmentioning
confidence: 99%
“…This arises because a forced wave approaching the breakpoint on a steep beach will be smaller than on a beach where the bound wave has developed over a long run of incident wave groups over shallow water before reaching the break point. Comparing measurements of total infragravity wave energy in 15 m depth and 5 m depth off the Californian coast, Thomson et al (2007) found a best fit dependence of between h À1/2 and h À1 , and a scatter of values mostly confined between these limits; none of the measurements came close to an h À5 dependence. However, it should be noted that the dependence of b b on the inverse of the wave height (through the breakpoint depth) appears contrary to Baldock's (2006) suggestion since it increases the relative contribution of the bound wave for waves breaking in deeper water.…”
Section: Magnitude and Cross-shore Pattern Of Infragravity Wave Energymentioning
confidence: 92%